Future Trends of Smartphone Application Intention to Use: Expansion of the Technology Acceptance Model - Alghizzawi, Mahmoud; Omeish, Fandi; Abdrabbo, Tariq; Alamro, Ahmed; Al Htibat, Ameen; Abd Ghani, Mazuri (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The emergence of smartphone applications has affected all types of industries. Rapid smartphone adoption has introduced a variety of mobile applications into the consumer market, transforming the way consumers perform various daily tasks and activities. As is the case in the tourism industry, through the positive features provided by smart phone applications, the tourism sector constitutes a major factor in Jordanian national income. Today, Jordan has the highest percentage of mobile application users, with high usage rates of mobile application features. However, tourism in Jordan is still suffering. Therefore, this study was conducted to examine the influence of smartphone application features, perceived usefulness, ease of use, and word of mouth (WOM) on the intention to use mobile applications in the Jordanian tourism industry. This study adopted a quantitative approach. It was based on a sample collected from tourists in Jordan using a self-administered questionnaire. A total of 420 copies of the questionnaires were distributed. The research model was empirically tested using structural equation modeling (SEM). SEM findings revealed that approximately 80% of the variance in intention to use mobile apps was accounted for by mobile app features, perceived usefulness, perceived ease of use, and positive WOM. The results showed that perceived usefulness and perceived ease of use were significantly related to WOM. The results of this research provide managerial guidelines for developing effective strategies for mobile applications in the Jordanian tourism industry.